Echocardiography and the general physician. Issue 940 (17th February 2004) - Heatlie, G J; Giles, M
Abstract : Doctors from many medical specialties request echocardiography as part of their assessment of patients with a wide range of pathology. Recent advances in the technology and techniques of echocardiography are discussed. The role of echocardiography in acute medicine is reviewed and its place in general medicine is also discussed.